The Effect of Enzyme, Time and Temperature on the Properties of Hydrolyzed Protein of Viscera Grass Carp (Ctenopharyngodon idella) - Atena Rafatinia; Laleh Roomiani (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2018)
The purpose of this study was to investigate the effect of enzyme kind, time and temperature on the properties of viscera (Ctenopharyngodon idella) hydrolyzed proteins. In this study, viscera was subjected to hydrolysis by alkalase, pepsin and flavourzyme commercial enzymes. Recycling efficiency and degree of hydrolysis obtained proteins and antioxidant activity DPPH in different conditions of the hydrolysis process at 15, 30, 60 min and three temperatures of 35, 45, 55 °C and between three enzymes with three replicates reviewed and compared. To investigate the existence or absence of significant differences between the values of each index, two-way analysis of variance and comparison of mean traits were used by Duncan test. For all enzymes used in this study, by increasing the time and temperature of hydrolysis, the amount of protein recovery and degree of hydrolysis and antioxidant activity increased, and the highest of these two indices for all three enzymes at 55 °C and in the time was 60 min and the lowest was observed at 35 °C and at 15 min. Also, the results showed that among the three enzymes studied, alkalase was similar in temperature to different pepsin and flavourzyme enzymes, with protein recovery and higher degree of hydrolysis and antioxidant activity. The highest protein digestion was related to the alkalase enzyme at 55 °C and 60 min (54.52±0.11%), and the lowest was obtained at 35 °C and 15 min. The results showed that the use of alkalase enzyme to produce hydrolyzed protein from grass carp was better in terms of recycling efficiency and degree of hydrolysis and antioxidant activity.